Survey on Security Challenges in Warning Message Dissemination and Possible Solutions - Balakrishnan, Salini; Tripti , C.; Cyriac, Robin (Asian Journal of Engineering and Applied Technology, 2014)
The recent advances in the area of Wireless Communications in Vehicular Ad-hoc Networks (VANET) have brought an emerging platform for both industrialists and for researchers. VANET possess a dynamic topology with multi-hop networks leading to an infrastructure less nature. Communication happens in two ways, one between the moving vehicles and with the Road Side Units (RSU). The usage of wireless medium would surely make it vulnerable to different attacks. By enabling prompt and correct warning messages on road conditions, accident cases etc. VANET can be used to save lives of people, which is the most important application of VANET. Distributing warning messages over a long range is however a very challenging task since message integrity has to be ensured. Also for making the system more reliable nonrepudiation should also be included in the security module. A survey of security issues in notification and warning message dissemination is done in this paper.